Genome size variation in Central European species of Cirsium (Compositae) and their natural hybrids - Bures, Petr; Wang, Yi-Feng; Horova, Lucie; Suda, Jan (Annals of botany, 2004)
BACKGROUND AND AIMS: Nuclear DNA amounts of 12 diploid and one tetraploid taxa and 12 natural interspecific hybrids of Cirsium from 102 populations in the Czech Republic, Austria, Slovakia and Hungary were estimated. METHODS: DAPI and PI flow cytometry were used. KEY RESULTS: 2C-values of diploid (2n = 34) species varied from 2.14 pg in C. heterophyllum to 3.60 pg in C. eriophorum (1.68-fold difference); the 2C value for the tetraploid C. vulgare was estimated at 5.54 pg. The DNA contents of hybrids were located between the values of their putative parents, although usually closer to the species with the smaller genome. Biennial species of Cirsium possessed larger nuclear DNA amounts than their perennial relatives. Genome size was negatively correlated with Ellenberg's indicator values for continentality and moisture and with eastern limits of distribution. A negative relationship was also detected between the genome size and the tendency to form natural interspecific hybrids. On the contrary, C-values positively corresponded with the spinyness (degree of spinosity). AT frequency ranged from 48.38 % in C. eriophorum to 51.75 % in C. arvense. Significant intraspecific DNA content variation in DAPI sessions was detected in C. acaule (probably due to the presence of B-chromosomes), and in tetraploid C. vulgare. Only the diploid level was confirmed for the Pannonian C. brachycephalum, generally considered to be tetraploid. In addition, triploidy was discovered for the first time in C. rivulare. CONCLUSIONS: Considerable differences in nuclear DNA content exist among Central European species of Cirsium on the diploid level. Perennial soft spiny Cirsium species of wet habitats and continental distributions generally have smaller genomes. The hybrids of diploid species remain diploid, and their DNA content is smaller than the mean of the parents. Species with smaller genomes produce interspecific hybrids more frequently.
Keywords: druhová specificita; Cirsium; Genome, Plant; genom rostlinný; Cell Nucleus; buněčné jádro; Species Specificity; chromozomy rostlin; Flow Cytometry; Chromosomes, Plant; DNA rostlinná; DNA, Plant; průtoková cytometrie; Hybridization, Genetic; Diploidy; hybridizace genetická; Polyploidy; diploidie; polyploidie